The Relationship of Mean Arterial Pressure Variability to Hematuria and Microalbuminuria in Hypertensive Patients at Abdul Moeloek Regional Hospital, Lampung: Ade Yonata, Nurul Islamy, Khairunnisa Berawi, Efriyan Imantika - Nurul Islamy; Ade Yonata (Fakultas Kedokteran, 2025)
Hypertension is a major risk factor for progressive cardiovascular and chronic kidney disease. Kidney complications from hypertension are characterized not only by a decrease in the glomerular filtration rate but also by the appearance of early kidney damage markers such as hematuria and microalbuminuria. One important factor influencing kidney damage in hypertensive patients is blood pressure variability, particularly Mean Arterial Pressure (MAP), which reflects the perfusion pressure of vital organs, including the kidneys. This was an observational analysis study with a cross-sectional approach using secondary data in the form of a review of medical records collected from January to December 2024 at Abdul Moeloek Regional Hospital. Sampling was conducted using a purposive sampling technique, with 35 participants meeting the inclusion and exclusion criteria. Data were analyzed using the Chi-square test and bivariate analysis. The results of this study indicate a relationship mean arterial pressure variability to hematuria (p=0.004) and microalbuminuria (p=0.003) in hypertensive patients at Abdul Moeloek Regional Hospital. Abdul Moeloek, Lampung